The factors influencing customer satisfaction in hotel industry (case study: Hotel Seri Malaysia Sungai Petani) / Norazidah Ahmad - Ahmad, Norazidah (Faculty of Business Management, 2015)
The purpose of this research is to study on the factors influencing customer satisfaction in hotel industry. There are some factors that influence customer satisfaction which consists of facilities, prices and services. The method used in this research is simple random sampling method whereby the respondent of the research consists of guest who come to hotel Seri Malaysia. Data were collected by using the questionnaire that given to the respondents who are willing to answers. Data that has been collected is analysing by using SPSS software to measure the variable for the research. However, the result shows that only two variables that have a significant relationship between independent variable and dependent variable. The facilities and services only have a significant relationship with customer satisfaction in hotel industry